Effect Of Selected Shading Devices On Office Room Temperature - A. Wahhad, Ali Mohamed (2008)

(untitled)
This study investigated the effects of selected shading devices on office room temperature at Universiti Putra Malaysia. The experimental and simulation results were presented to show the thermal effects of coating systems used. Initial work for a duration of two months showed that high temperatures occurred at 10:00, 1200 and 14:00 hours. This frequency of measurement is similar to that of Etzion and Erell (2000). Thermocouple wires were used to measure the air temperature in an office of size 4.03 m x 3.82 m x 2.60 m (length x width x height). The window was a vertical glass plate with thickness 5 mm, height 1.53 m and width 2.12 m and it was facing northeast. Coating materials used were plain glass pane thickness 5 mm (control), tinted film, silver film, and blinds. Results showed that the differences in temperature between the inside and outside of the office were 4.4oC, 3.8oC, 3.5oC and 2.9oC for silver film, blinds, tinted film and clean glass (5 mm), respectively. Comparison between simulated and experimental results showed a reasonable agreement, ranging between 0.2 to 10 %. The external air velocity ranged between 0.19 and 0.45 ms-1 and relative humidity between 22.7% and 77.5 %, while the average air velocity in the office ranged from 0.03 to 0.05 ms-1 and relative humidity from 57.2 % to 66.8 %. The simulated results for internal air temperatures of the office ranged from 28oC to 29oC. In terms of cost, the blinds gave value for money with every temperature drop for temperature difference between internal and external temperatures. In addition the blinds could be easily fixed.